1997
DOI: 10.1097/00000658-199709000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Six Hundred Fifty Consecutive Pancreaticoduodenectomies in the 1990s

Abstract: This single institution, high-volume experience indicates that pancreaticoduodenectomy can be performed safely for a variety of malignant and benign disorders of the pancreas and periampullary region. Overall survival is determined largely by the pathology within the resection specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

77
1,164
18
79

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,722 publications
(1,338 citation statements)
references
References 37 publications
77
1,164
18
79
Order By: Relevance
“…About 30% of the patients underwent a palliative resection, a percentage not different from the previous period in this institution and from the literature [1,5,6,10,11]. In a recent series of 650 consecutive resections from Johns Hopkins positive margins were found in 29% of the 282 patients with a pancreatic carcinoma [12]. As shown in Table 3, the postoperative complications, mortality, and hospital stay after palliative resection were no higher than after radical resection.…”
Section: Postoperative Complications and Mortality After Palliative Smentioning
confidence: 59%
“…About 30% of the patients underwent a palliative resection, a percentage not different from the previous period in this institution and from the literature [1,5,6,10,11]. In a recent series of 650 consecutive resections from Johns Hopkins positive margins were found in 29% of the 282 patients with a pancreatic carcinoma [12]. As shown in Table 3, the postoperative complications, mortality, and hospital stay after palliative resection were no higher than after radical resection.…”
Section: Postoperative Complications and Mortality After Palliative Smentioning
confidence: 59%
“…However, cancer‐free resection margins at the bile duct stump are difficult to achieve because of longitudinal extension, which is one of the prominent characteristics of extrahepatic cholangiocarcinoma 11, 12. Ductal resection margin status is an established prognostic indicator,13, 14 and survival following resection in patients with positive ductal margins has generally been deemed unsatisfactory 10, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25. In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not.…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients with pancreatic cancer present with advanced disease due to early lymphatic and hematogenous spread and the tendency toward infiltrative growth; therefore, only 10 -30% of pancreatic cancers are considered to be resectable at the time of diagnosis (4,6 -9). Pancreaticoduodenectomy, even with an expert surgeon's hands, carries a 5% mortality and postoperative morbidity approaching 50% (2,5,7,9). Therefore, early diagnosis and an accurate assessment of tumor resectability are an essential step in the treatment planning so that unnecessary surgical procedures can be avoided (8,10 -15).…”
mentioning
confidence: 99%